4CPS-070 Does antibiotic consumption predict the incidence density of healthcare-associated infections?. (March 2019) - Peric, A; Vezmar Kovačevič, S; Milenkovič, B; Šuljagič, V
Abstract : Background: The decrease in healthcare associated infections (HAI) in intensive care units (ICUs), related to surgical-site infections (SSIs) and Clostridium difficile infections (CDIs), as well as antibiotic consumption, are the main goals in the hospital setting. Purpose: The aim of this study was to evaluate the antibiotic consumption, and to relate it with HAI incidence density (ID) and incidence rate (IR). Material and methods: The study was conducted from 2011 to 2016 in a tertiary hospital. Through regular hospital surveillance, we identified all patients with a new HAI. Data on the use of antibacterials for systemic use were expressed as defined daily dose per 100 bed days (DDD/100 BD). Results: The highest ID of HAIs was observed in patients in surgical ICUs (25.5–47.2/1000 patient days), while the IR of SSI was 3.7%. Moreover, the highest ID of CDI in medical patients was 6.2, while in surgical patients it was 4.3 per 10 000 patient days, while, at the same time, the antibiotic consumption was the lowest (31.2 DDD/100 BD). The most frequently used antibiotics, on average, were cephalosporins, aminoglycosides and carbapenems (16.0±2.3, 4.8±0.7, 4.3±0.7 DDD/100 BD, respectively). The decrease in use of glycopeptides and fluorochinolones was predictive of higher ID of medical CDIs (p<0.05). Conclusion: The most frequently used antibiotics were not associated with HAIs. However, the decrease in use of glycopeptides and flurochinolones was associated with higher ID of CDIs. Simply decreasing the consumption of antibiotics with high risk for HAIs may not be sufficient. References and/or acknowledgements: 1. Berríos-Torres SI, Umscheid CA, Bratzler DW, et al. Centers for disease control and prevention guideline for the prevention of surgical site infection, 2017. JAMA Surg2017;152:784–91. 2. World Health Organisation (WHO) Collaborating Centre for Drug Statistics and Methodology. Guidelines for the ATC classification and DDD assignment, 2017. Oslo, 2016. 3. Davey P, Brown E, Charani E, et al. Interventions to improve antibiotic prescribing practices for hospital inpatients (Review). Coch Data Syst Rev 2017; 2:CD003543. 4. ECDC. European Surveillance of Healthcare-Associated Infections in Intensive Care Units – HAI-Net ICU protocol, version 1.02.2015. 5. Laine N, Hoppu K, Airaksinen M, Saxen H. Antimicrobial consumption in a tertiary children's hospital in Finland (2003–2013). Eur J Hosp Pharm 2016;23:266–71. No conflict of interest.